The Impact of Strategic Vigilance on Organizational Excellence in Jordanian Telecom Companies - Abu-Hamour, Husam; Al-Anaswah, Sura (The Arab Journal of Administration, 2023)
This study aimed to know the impact of strategic vigilance on organizational excellence in Jordanian telecom companies. On the analytical descriptive (quantitative) method, the statistical program (SPSS) was used to data analysis and test hypotheses. There is impact of the dimensions of strategic vigilance collectively and individually (competitive, technological, commercial, and environmental) on the dimensions of organizational excellence in terms of its collective and individual dimensions (leadership, organizational structure, services, human resources and knowledge), and the most important dimensions of strategic vigilance are environmental vigilance, competitiveness, technology, and finally commercial vigilance to achieve organizational excellence. The study recommends working on complementary events between strategic vigilance and risk management systems, supporting creativity and innovation, and establishing strategic alliances capable of keeping pace with changes in the business environment.